2019
DOI: 10.5812/aapm.93848
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nitroglycerine Infusion on Postoperative Pain in Lower Limb Surgery: A Clinical Double-Blind Study

Abstract: BackgroundAcute postoperative pain causes severe discomfort in patients accompanied by hemodynamic and metabolic instability.ObjectivesThe aim of this study was to evaluate the effects of nitroglycerin addition on the infusion of intravenous analgesia pump in patients with lower limb orthopedic surgery.MethodsThis study was a double-blind clinical trial conducted on 75 patients with lower limb fracture. Patients were randomly assigned to receive three regimens for postoperative pain control via intravenous ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A meta-analysis of 865 patients enrolled in four clinical trials addressing the impact of the addition of IV Acetaminophen to analgesia after total hip and knee arthroplasty concluded that there was a significant decrease in pain score and opioid consumption on post-operative days 1 to 3. Nausea and vomiting were decreased in the groups who received IV Acetaminophen (22,26).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A meta-analysis of 865 patients enrolled in four clinical trials addressing the impact of the addition of IV Acetaminophen to analgesia after total hip and knee arthroplasty concluded that there was a significant decrease in pain score and opioid consumption on post-operative days 1 to 3. Nausea and vomiting were decreased in the groups who received IV Acetaminophen (22,26).…”
Section: Discussionmentioning
confidence: 88%
“…Remifentanil is an ultra-short-acting opioid that facilitates hemodynamic and neurologic management. Since the half-life of remifentanil is short, it is better to use it as an infusion (22,23). The main problem of remifentanil-based anesthesia is the rapid disappearance of its analgesic effect after the end of infusion, which may cause the development of acute opioid tolerance (AOT); because of the pharmacokinetic properties of remifentanil, the incidence of AOT would be predictable (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…In another study ( 10 ) three groups were investigated, including A (fentanyl 10 µg/kg + 10 mL distilled water), B (fentanyl 10 µg/kg + nitroglycerin 500 µg), and C (fentanyl 10 µg/kg + nitroglycerin 1000 µg), and it was found that the group C had the lowest pain. Although the effect of nitroglycerin on hemodynamic was higher in this situation, but no significant difference was observed between these groups in terms of MAP and HR.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the consumption of perioperative opioids, various drugs and methods have been studied to date, including non-opioids, adjuvants, and regional, peripheral, and neuraxial blocks. Nevertheless, the application of each of these methods and drugs requires specific knowledge, experience, equipment, arrangements, and care (3)(4)(5)(6)(7). Many clinical studies have been published on the application of multimodal analgesia in a variety of surgeries.…”
mentioning
confidence: 99%